Heart Health at the Frontline: A Study on Hypertension and Prehypertension involving Healthcare Staff of a Tertiary Care Hospital - Savalia, Dr. Malay; Parmar, Dr. Pravin; Singh, Aditi; Jain, Akshat; Alwe, Saurabh; Deswal, Aman; Banerjee, Amartya (International Journal of Innovative Research in Medical Science, 2024)
Background: Hypertension, a major public health concern worldwide, affects individuals across various professions, including healthcare workers. This study aims to estimate the prevalence of hypertension and prehypertension among healthcare staff working at a tertiary care hospital and assess the associated risk factors. Aims and Objectives: To find prevalence of hypertension and prehypertension and its link with various demographic variables among study population. Settings and Design: A cross-sectional study was conducted at the tertiary care hospital. Methodology: A cross-sectional study was conducted, including a representative sample of healthcare staff. Data on demographics, lifestyle factors and blood pressure measurements were collected. The prevalence of hypertension and prehypertension was estimated, and significant risk factors were identified. Statistical analysis used: One-way ANOVA test and Chi square test were used to compare different variables. Results: Out of total study participants 38.02% were males and 61.98% were females. Among all the continuous variables included, weight, BMI, waist circumference and systolic BP and diastolic BP showed significant association. Among all the non- continuous variables included, monthly family income, place of residence, education, post in current occupation, use of extra salt in diet and habit of doing regular exercise showed significant association. Conclusions: The study showed age, weight, BMI, waist circumference, place of residence, education, post at workplace, monthly family income, use of extra salt in diet and habit of exercise were strongly associated with blood pressure and were better potential predictors of risk for hypertension and prehypertension than the other indices tested.